Chromosome 11q13 amplification as a decision-making biomarker for anti-PD-1 immunotherapy in recurrent or metastatic head and neck squamous cell carcinoma: a prospective cohort study - Jiang, Wen; Dou, Shengjin; Zhang, Lin; Dong, Minjun; Li, Jiang; Wang, Ge; Gu, Ziyue; He, Yining; Sun, Debin; Li, Rongrong; Zhu, Guopei (Frontiers in Immunology, 2025)
BackgroundAnti-programmed cell death protein 1 (anti-PD-1) immunotherapy has shown efficacy in recurrent or metastatic head and neck squamous cell carcinoma (R/M HNSCC), but current biomarkers have limitations in predicting immunotherapy response accurately. Chromosome 11q13 amplification, prevalent in HNSCC, has been associated with reduced efficacy of anti-PD-1 therapy. This study aims to prospectively evaluate 11q13 amplification as a biomarker for guiding first-line treatment in R/M HNSCC. We hypothesize that excluding patients with 11q13 amplification from anti-PD-1 therapy may enhance survival outcomes.MethodsThis single-institution prospective cohort study included previously untreated patients with R/M HNSCC. Based on 11q13 amplification status, non-amplified patients received PD-1 inhibitor monotherapy or combination therapy with chemotherapy, while amplified patients were treated with cetuximab and chemotherapy. Nedaplatin was used in place of cisplatin if necessary. Ten 11q13-amplified patients receiving anti-PD-1 therapy served as an external control group.ResultsBetween August 2020 and June 2023, 75 patients were enrolled prospectively, and an additional 10 patients with 11q13 amplification were included as an external control. Among R/M HNSCC patients without 11q13 amplification who received anti-PD-1-based therapy, the objective response rate (ORR) was 72.5%, with a median progression-free survival (PFS) of 14.3 months and an overall survival (OS) of 38.2 months. These survival outcomes were superior to those seen in other cohorts within this study and reported in other trials.ConclusionsOur study suggests that 11q13 amplification status could serve as a valuable biomarker for first-line treatment decisions in R/M HNSCC. Patients without 11q13 amplification exhibited better responses to anti-PD-1 therapy, providing insights into optimizing treatment strategies.Clinical trial registrationChinese Clinical Trial Registry identifier, ChiCTR2000035635.